FORMULATING STRATEGIES TO IMPROVE FOOD SAFETY OF BAKERY SMALL-MEDIUM ENTERPRISES THROUGH GOOD MANUFACTURING PRACTICE - Yandra Arkeman, Triningsih Herlinawati, Dhani S. Wibawa, Himawan Adinegoro TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
The food industry in Bogor is dominated by small enterprise (96%). Problems on small enterprise, among others, the emergence of food safety issues due to low sanitation and hygiene practices. Based on data from outbreaks (epidemics) of Indonesia in 2001-2006, it is known that the major cause of poisoning was due to microbes and were common in food products produced by small-medium enterprise (SME) and catering. The objective of this research was to formulate strategy for improving food safety based on implementation of Good Manufacturing Practices (GMP). This paper presents I-SWOT analysis regarding the implementation of GMP on bakery small-medium enterprises in Bogor. SWOT analysis for the strategic environmental factors identified the significant aspect of the supporting elements, constraints, and the groups of the alternative strategy. Complete analysis of this research resulted in five alternatives formulation strategies for improving food safety based on implementation of GMP, with considering respective limitation.Keywords: bakery, good manufacturing practices, interpretative structural modelling, small-medium enterprises, SWOT